The algoritms of determination of structural invariants of causality, controllability, reachability, observebility and restorability for controlled inputoutput dynamic systems; Abstracts the First Korea-Russia Symposium on Science and Technology, Sept. 29- Oct. 3, 1997 - Malishenko (Malyshenko) A. M. Alexanedr Maximovich (1999, 1999)
В фонде НТБ ТПУ отсутствует